Innovation, localized externalities, and the British Industrial Revolution, 1700-1850 - Ugo M. Gragnolati; Alessandro Nuvolari (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
We study the determinants of the spatial distribution of patent inventors at the county level for Great Britain between 1700-1850. Our empirical analysis rests on the localization model by Bottazzi et al. (2007) and on the related estimation procedure by Bottazzi and Gragnolati (2015). Such an approach helps in particular to discriminate the role of localized externalities against other descriptors of county attractiveness. Our results show that, while the underlying geography of production remained a strong determinant of inventor location all throughout the industrial revolution, the effect of localized externalities among patent inventors went from being nearly absent in the early phases of industrialization to becoming a major driver of inventor location. In particular, local interactions among the ''mass'' of generic inventors turn out to be at least as important as interactions with ''elite'' inventors.
Keywords: C31; N73; N93; O33; R12; 330; Inventor location; Patents; Localized externalities; Industrial Revolution